A Study of the Performance of Highly-Educated Immigrants in the Canadian Labour Market - Li, Xiaoxiao (Université d'Ottawa | University of Ottawa, 2012)
With 2006 Census data, this paper uses wages and salaries, employment, work in a professional occupation, and self-employment status as labour market outcomes to examine the economic performance of highly-educated immigrants in Canada. The aim is to identify the factors and deterninants most likely leading to a successfull integration in the Canadian labour market. Geographical, socio-demographic, immigration and educational characteristics are taken into account in the models. Those factors are examined for males and females respectively to see if the influences on outcomes differ by gender This study finds that married male immigrants who received their doctoral degrees in science and technology in Canada or the U.S.A earned the highest income and are the most likely to work in a professional occupation. Similar characteristics apply to female immigrants; however, contrary to most studies, the presence of children is not a barrier for female access to a professional occupation. Furthermore, highly-educated immigrants with high qualifications are relatively more likely to engage in self-employment and, surprisingly, the country of origin does not significantly affect the likelihood of being self-employed for males.